PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN DIVIDEN, PERTUMBUHAN PERUSAHAAN, PROFITABILITAS DAN STRUKTUR ASET TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sonny Indra Permana, 10.05.52.0098; Lisiantara, Greg. Anggana (Students Journal of Accounting and Banking, 2014)
This researchâs purpose it to analyze factors that impact debt policy on manufacturing companies that registered on BEI. Population on this research is a manufacturing companies that registered on indonesian stock exchange (BEI).The sample used on this research is about 99 companies that observed on 2010 until 2012 with purposive sampling technique. The independent variabel on this research are Managerial Ownership, Institutional Ownership, Dividend Policy, Company Growth, Profitability and asset structure. While the dependent variable is proxied using the Debt Policy (DER). The analysis used multiple linear regression.The results showed that the Institutional Ownership, Dividend Policy, and Profitability does not affect the Debt Policy (DER). Meanwhile Managerial Ownership, Company Growth, And Asset structures that affect company Debt Policy(DER).Keywords: Managerial Ownership, Institutional Ownership, Dividend Policy, Company Growth, Profitability Asset Structure and Debt Policy (DER)